Using podcasting to enhance the experiences of apprentice paramedics in higher education - Wilkinson, James; Copson, Joe (International Journal of Practice-based Learning in Health and Social Care, 2025)
Podcasts are being incorporated into more healthcare education programmes, as increasing availability of resources and flexibility to learn whilst on the move become key benefits to this form of teaching (Kirkwood & Price, 2014). Podcasts are considered valuable tools in education, allowing listeners to multi-task during episodes and use playback functions to aid understanding (Goldman, 2018). The aim of this action research establishes the critical question: ‘Does the use of podcasting within apprentice paramedic education enhance learner experience?’. Action research allows an individual to reflect on their own practice, act on feedback and observe changes in their own development (Cohen et al., 2018). For the intervention, in replacement of a live teaching session, 60 apprentice paramedics listened to three podcast episodes uploaded to their virtual learning environment. Qualitative data was collected about this experience through an online survey, before thematic analysis was completed on the responses. Ethics approval was obtained before data collection, with 21 fully completed responses. Three themes were identified from survey results: Overall experience in Higher Education, Accessibility and Quality of podcasts. All participants felt comfortable using the technology involved with podcasts and students had a generally positive experience with the content for this session. The majority agreed they preferred podcasts to traditional lectures or Powerpoint, and two-thirds were able to complete other tasks whilst listening to the intervention. However, not all students feel podcasts should be used in replacement of lectures and some argue that traditional methods still best suit their needs.